PENGARUH DISINFORMASI VAKSIN COVID-19 TERHADAP KECEMASAN WISATAWAN JAKARTA-BALI - Rifka Nayla Azkia; Windhiadi Yoga Sembada; Ratu Nadya Wahyuningratna (Jurnal Pustaka Komunikasi, 2022)
This study aims to determine how much vaccine disinformation influence the anxiety level of Jakarta-Bali tourists by using Information Integration Theory. The method used is descriptive quantitative using primary and secondary data sources. The technique of collecting data by collecting samples was done by purposive sampling. Researchers used the stages of validity and reliability testing to test the questionnaire instrument that has been made. Stages of data analysis using correlation test, coefficient of determination test, regression test, and hypothesis test. The final result of this study shows that there is a correlation between variable X and variable Y which has a strong relationship with a correlation value of 0.656 while the rest can be influenced by other factors. Then for the results of the hypothesis test, namely H0 is rejected and H1 is accepted, which means that there is an effect of disinformation on the COVID-19 vaccine on the anxiety of Jakarta-Bali tourists.